Psychoanalytic Psychotherapy as a Method of Treatment for a Special Educator Experiencing Disengagement in Relation to her profession: A Case Study (Global Journal of Human-Social Science, 2018)
The present case study focuses on a special educator working with children with psychosis, named Sophie, who engaged in two years of psychoanalytic psychotherapy in order to resolve feelings of distress, anxiety, low self-esteem. Her mental state is examined in relation to the nature of her profession, the transference children experience with their educators, the emotional bond created and the mental representations she had created for her work. More specifically, we considered the role played by mental representations and symbolization in the way an educator addresses their profession and distinguishes between their internal representations and external reality. Methods of psychoanalytic psychotherapy were adopted in order to allow her to improve her mental state, such as self-reflection and self-analysis. Progress is documented through two scales, the Multimodal Questionnaire of Professional Engagement and the Beck Depression Inventory, and two projective tests, the Draw A-Tree test, and the Draw-A-Person-In-The-Rain test, which were employed at the beginning and the end of the therapeutic process. Findings regarding Sophie's improvement are discussed.
Keywords: special educator; psychotic children; psycho-analytic psychotherapy; representations; symbolization; mentalization; scales; projective tests